Traveling Wave Solutions of Reaction-Diffusion Equations Arising in Atherosclerosis Models - Narcisa Apreutesei (Mathematics, 2014)
In this short review article, two atherosclerosis models are presented, one as a scalar equation and the other one as a system of two equations. They are given in terms of reaction-diffusion equations in an infinite strip with nonlinear boundary conditions. The existence of traveling wave solutions is studied for these models. The monostable and bistable cases are introduced and analyzed.